Kehidupan Ibu Rumah Tangga yang Bekerja sebagai Pengolah Ikan Asin dalam Meningkatkan Sosial Ekonomi Keluarga di Pasar Belakang Kota Sibolga - Simbolon, Nelly (JURNAL DIAKONIA, 2022)
The majority of people in the back market of Sibolga work as salted fish processors to fulfill the daily needs of their families. Every day the people who work there come to manage the fish caught by the fishermen become salted fish. Housewives work as salted fish processing workers in order to improve the family’s social economy. Working outside the home becomes a dual role for housewives which will have an influence on relationships with family. However, for the sake of a good social economy, housewives carry out dual roles in the hope of changing the standard of family life.